UTILIZATION OF LOCAL MICROORGANISMS (MOL) IN LIQUID FERTILIZER PRODUCTION ACTIVITIES IN SAKRA VILLAGE - Astuti, Sri Puji; Marpatulliana, Marpatulliana; Suparman, Haris; Aji, Lalu Dimas Akbar Rido; Novida, Sari (Jurnal Abdi Insani, 2022)
Household waste is a type of organic waste, it has the shape of pieces of leftover fruit, vegetables, and natural materials that cannot be reused. Kitchen waste decomposes quickly, becoming a source of germs and disease. Kitchen waste was contained by local microorganisms (MOL) that can be managed carefully, as an independent effort to manage household-based organic waste. Sakra Village, one of the villages in Sakra District, has not been optimal in managing household waste into MOL. As a result, it is necessary to carry out socialization and training in the village. The community service aims to socialize how to produce MOL by using rice waste, and the MOL can be optimized as liquid fertilizer. The activity began with an inventory of types of household waste. Material dissemination applies the Forum Discussion Group (FDG) method by dividing groups based on the age of the audience. The procedure for making MOL made from rice and continuous application of liquid fertilizer was delivered using a demonstration technique in each FDG group. The end of the activity was an evaluation of the activities through the interview. Nine types of kitchen waste were commonly produced, including rice waste, fish dregs, fruit peels, bamboo shoot dregs, shrimp paste dregs, and vegetable scraps. Socialization materials regarding the importance of managing household organic waste, the introduction of types of organic waste as MOL material, and techniques for making MOL made from rice. The application of liquid MOL fertilizer was continued on vegetable crops. The results of the evaluation showed that 82% of participants considered the use of the FDG method to be more effective. There were 72% of the audience were very enthusiastic in asking questions and participating in all step activities till the end, and 70% of attendance practiced the material independently, the achievement became an indicator of the success of the activity. Participants have been able to make liquid MOL from kitchen waste, and have been able to apply it as liquid fertilizer to plants.